Luminescent Solar Concentrator Greenhouses for Concurrent Energy Generation and Lettuce Production in the United States - Kristine Loh; Kale Harbick; Nathan Eylands; Uwe Kortshagen; Vivian Ferry (AgriVoltaics Conference Proceedings)
Meeting the needs for both renewable energy production and increased food supply to sustain growing communities remains a global challenge. Agrivoltaic greenhouses can meet these dual needs in one plot of land, mitigating land competition. Luminescent solar concentrators (LSCs) benefit these systems by providing additional design flexibility for crop-specific spectrum modification while allowing sufficient light transmission for crop growth. Silicon quantum dots (Si QDs) have received growing interest as a material candidate for LSC greenhouses as well. We present an investigation into the impact of Si QD film concentration on the energy demands of an LSC greenhouse in Phoenix, Arizona through a comprehensive modelling framework. We then expand upon one Si QD concentration and simulate LSC greenhouses in 48 locations across the United States. We demonstrate LSC greenhouses can supply their annual energy demands in warm climates, where greenhouse heating demands remain low. LSC greenhouses can also be as profitable as the conventional glass greenhouse if the crop yield remains comparable or if the greenhouse can benefit from net metering.